Peran Asistensi Mengajar Dalam Studi Etnografi Pelatihan Membatik: Upaya Pelestarian Budaya Lokal Di Sds Soekarno Hatta Pada Peringatan Hari Batik Nasional - Berta Apriza; Sogol Rismawan; Jhovin Trio Fikas; Afifah Afifah; Diana Franikawati; Widya Lestari; Devy Aulia Saputri (Universitas Sumatera Barat, 2026)
Batik training is one of the efforts to preserve local culture, which can be introduced to elementary school students from an early age. This study aims to analyze the role of the Teaching Assistance program from Universitas Muhammadiyah Kotabumi in implementing tie-dye batik activities based on an ethnographic study at SDS Soekarno Hatta during the National Batik Day celebration. The research method used was qualitative descriptive with a case study approach, involving four sixth-grade classes, interviews with teachers and students, as well as audiovisual documentation during the activities. The results show that students were actively and enthusiastically involved in every stage of the training, from tying techniques to fabric dyeing, which enhanced their creativity and understanding of local culture. The students gained hands-on experience in teaching and applying an ethnographic approach, while teachers were inspired to integrate cultural learning into the curriculum. In conclusion, the collaboration between the university and elementary school through the teaching assistance program is effective in preserving local culture while developing students’ skills and character